Impact of Tharthar Arm on the Composition and Diversity of Rotifera in Tigris River North of Baghdad, Iraq - Majeed, Osama S.; Nashaat, Muhanned R.; Al-Azawi, Ahmed J. M. (Iraqi Journal of Science, 2022)
This study was conducted to evaluate the effects of Tharthar Arm on the composition and diversity of Rotifera in Tigris River. Six sampling sites were selected, two on Tharthar Arm and four along the Tigris River, one before the confluence as a control site and the others downstream of the confluence. Seventy-seven species of Rotifera were identified in Tigris, whereas, 60 in the arm. The results showed that low density of Rotifera in Tharthr Arm decreased the density in Tigris from 239812.4 upstream of the confluence to 223315.5 at immediate downstream of the confluence. It also declined the mean values of richness, evenness and Shannon diversity indices from 5.19, 0.69 and 2.14 bit/Ind., before the confluence to 3.97, 0.73 and 2.00 bit/Ind. below the confluence, respectively. Moreover, the highest similarity value was between sites 1 and 6 reached 83.27%, while the lowest value was between sites 1 and 2 recorded as 60.52%. For constancy index, the highest value was 14 in site 1 and the lowest was 8 in site 2.